Addressing Local Sustainability: Strategic Thinking in the Making - Kettunnen, Pekka; Heino, Hanna; Rasinkangas, Jarkko; Jauhiainen, Jussi S. (Scandinavian Journal of Public Administration, 2020)
Local governments are key actors in sustainable development. However, comprehensive achievements in relation to sustainability remain limited, even though sustainable development has been on the agenda for decades. Achieving sustainability requires future-oriented thinking, proper long-term development strategies, and concrete action. Developing strategy is not enough to ensure achievement, and local governments should therefore engage in strategic thinking as a method of promoting sustainability at the local level. Based on data collected through a survey of 113 Finnish municipalities, this research used statistical methods to empirically analyse the extent to which the municipalities employed strategic thinking. The results showed that the municipalities which performed well in various aspects of strategic thinking were also more engaged in sustainability issues than those municipalities that were not strategically oriented.